Boundary-value problem for nonlinear degenerated parabolic equations with variable delay - Il’nyts’ka, О. V.; Bokalo, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study boundary-value problem with Dirichlet conditions for nonlinear parabolic equations with variable delay (i.e.,delay is a function of time) and degeneration at the initial time. The existence and uniqueness of the classical solution ofthis problem are proved. A priori estimates of this solution are obtained.